DEVELOPING STUDENTS’ CREATIVITY THROUGH THE COURSE OF FUNDAMENTALS OF MATERIALS SCIENCE - Pulotov Adxam Abduraxmonovich (International Journal of Literature and Language Studies, 2026)
This article discusses the issue of developing students’ creativity through the Fundamentals of Materials Science. It analyzes ways to form students’ creative thinking, independent problem-solving skills, and ability to generate new ideas by effectively using modern pedagogical technologies, interactive methods, and practical training sessions in the teaching of materials science. It also highlights the importance of laboratory work, project-based tasks, and innovative approaches in increasing students’ creative activity. This article serves to develop students’ creative potential and guide them toward innovative thinking in the process of teaching materials science.